Methods of standardizing processes of construction of monolithic building structures - Molodid, O.S.; Shandra, O.H. (Ways to Improve Construction Efficiency, 2023)
The existing standardization systems of labor processes in the construction industry are considered. During the last twenty years, there has been significant progress in the development of construction technologies, which is associated with the rapid development of materials, structures and means of mechanization. BIM design technologies and management of construction projects are developing very quickly. There is a lag in the development of construction process standardization systems, which holds back the creation of electronic standards databases. The importance of rationing the time for the execution of construction processes is increasing. The existing systems of standardization of construction processes have a number of shortcomings and require changes in the approach to standardization. The breakdown of processes into components should be finer. The standards should allow changes to be made to the project in accordance with the introduction of new construction technologies, materials, mechanisms, and equipment. The main shortcomings of the existing standardization systems are considered on the examples of the installation processes and dismantling of floor formwork. The analysis resulted in the statement that the existing norms do not correspond to the principles of variant design of technological processes, restrain the design development and management of construction projects. The foreign experience of standardizing processes in mechanical engineering, as in the industry that is a level above construction, is considered. There are certain advantages of the system for the production processes standardization of factory-made products, which allows some approaches to be used in the standardization of construction processes. One of the ways to solve the problems of normalization of construction processes is the possibility of combining normalization methods with the transition to the definition of time norms and norms of labor costs of smaller elements of technological processes, such as actions, sets of actions, operations. For this purpose, it is proposed to combine the elements of the method of microelement standardization with the method of developing maps of labor processes, which will allow to develop a new methodology of integer standardization of the processes of erecting monolithic buildings and structures.